Apports de l’archéobotanique à la compréhension de la Source des Roches, Chamalières (Puy-de-Dôme) - Béatrice Prat; Manon Cabanis (Revue Archéologique du Centre de la France)
Unusually high levels of tree pollen were revealed by palynology on the site of the Source des Roches in Chamalières (Puy-de-Dôme) for the very beginning of the Roman period. The site had yielded more than 3500 wooden offerings in the early 70s. Such a high density of woodland can be found nowhere else for the Second Iron Age and the Roman period, neither in the plain of Limagne, nor on the plateau of Les Dômes. The hypothesis of an open air sanctuary, first advanced by Anne-Marie Romeuf, director of excavation, is therefore reinforced by the pollen analysis which leads us to consider the possibility that a “sacred grove” made up principally of oaks was present. The correlation of the archaeobotanic data from palynology and paleœthnobotany contributes to the strengthening of the site’s knowledge from the landscape’s point of view. We also have a better understanding of the vegetal offerings associated with the wooden statues.